THE SPANISH GRAMMAR IN THE LITERARY AND LINGUISTIC FORMATION OF THE SPANISH –LITERATURE CARRER - Pérez González, Yeissett; Menocal Sardiñas, Ana (Atenas, 2014)
The teaching of Spanish grammar, promotes the linguistic and literary training of students, by integrating the content-form-context found in the relation of semantic, syntactic and pragmatic dimensions, therefore, being conducive of a general, integral education of professionals in language and literature. The contribution of the tools for language studying and exercising by means of the description, signification and contextualization of discourse’s linguistic structures and their contribution to the comprehension and construction within the process of meaning creation and comprehension, leads to the education of an efficient communicator, which holds communicative powers that will allow him or her to serve as a linguistic pattern at any educational level.